Amortecedor dinâmico viscoelástico com memória para vibrações de um edifício de pequeno porte - Lemos, Lidiane Azambuja (2013)
In this paper, we present the numerical analysis of the efficiency of a dynamic damper with memory viscoelastic material (VEMD) for application in the reduction of resonance states of small buildings, Modeled by plane frames subjected to dynamic excitations of an electric motor with limited power source and variable angular velocity (SNI – Non-Ideal System). Draws up a mathematical model of the complete system with four degrees of freedom: two related horizontal displacement and angular gantry plane and engine related to the two materials ADVM. Computational tests were performed using MATLAB ® based on the Runge-Kutta algorithm with adaptive step. The Analysis of the system behavior with and without control was performed using the tools of nonlinear dynamics, including: phase plane, time series, FFT and resonance curves.